Effectiveness Problem-Solving Techniques Through Group Guidance Services to Reduce Social Loafing - Putri, Miftahul Hasana; Syarqawi, Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research aims to determine the effectiveness of group guidance services through problem-solving techniques to reduce students' social loafing. The research method used is quantitative, with a pre-experiment design of one group pretest-posttest. The primary and secondary data used in this research are primary and secondary. Secondary data was obtained from documentation, while primary data was obtained through a questionnaire with a Likert scale. The population of this study was 63 students at MTs Islamiyah Hessa Air Genting. Sample as many as eight people who had social loafing behavior. Samples were taken using a purposive sampling technique. Data was collected through a questionnaire with a Likert scale. Data was analyzed using the Wilcoxon Signed Ranks Test with the SPSS For Windows Versions 22.0 statistics program. The results show that the significant value of Asymp. Sig(2-tailed) < 0.05, namely 0.012. This means that group guidance services through problem-solving techniques effectively reduce social loafing in students.